Analisis Efisiensi Biaya Persediaan Material Listrik dengan Metode EOQ, Safety Stock, dan Reorder Point - Ramdan, Mohamad Fatur; Satrio, Fabyan Hijri; Zahra, Astri; Andriansyah, Faisal Arip; Supriyati, Supriyati (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze the cost efficiency of electrical component material procurement at PT Kimindo Jaya Indonesia through the implementation of the Economic Order Quantity (EOQ), Safety Stock, and Reorder Point (ROP) methods. A quantitative approach was applied using data from ten key components used in the assembly process of power distribution panels. Calculations were conducted to determine the optimal order quantity, safety stock level, and reorder point. The findings indicate that implementing the EOQ, Safety Stock, and ROP methods reduced the company’s annual inventory cost from IDR 5,740,000 to IDR 3,900,000, achieving a 32% cost efficiency. These results highlight the importance of measurable inventory policies in maintaining supply continuity and cost efficiency in project-based companies. Future research is recommended to integrate digital forecasting systems to enhance material procurement accuracy.